Karakteristik Komposit Bioplastik dalam Variasi Rasio Pati Gadung (Dioscorea hispida D.) - Glukomanan dan Suhu Gelatinisasinya - Pratami, Ni Luh Feby Putri; Hartiati, Amna; Harsojuwono, Bambang Admadi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 2 (2021): JuniDO - 10.24843/JRMA.2021.v09.i02.p02, 2021)
This study aims to determine the effect of variations in the ratio of gadung starch (Dioscorea hipida D.) - glucomannan and their interaction on the characteristics of bioplastic composites and to determine the ratio of gadung starch (Dioscorea hipida D.) - glucomannan and its gelatinization temperature which gives the best characteristics of bioplastic composites. This study used a factorial randomized block design (RBD) with two factors. The first factor is the variation in the ratio of the gadung tuber starch - glucomannan which consists of 3 levels, namely (60:40), (50:50), (40:60). The second factor is the gelatinization temperature which consists of 3 levels, namely 75 ± 1oC, 80 ± 1oC 85 ± 1oC. Each treatment was grouped into 2 based on the time of the manufacturing process so that 18 experimental units were obtained. The variables observed were tensile strength, elongation at break, elasticity, and biodegradation time. The data obtained were analyzed of variant and continued with the HSD Tukey. The results showed that the ratio of gadung - glucomannan starch, gelatinization temperature, and their interactions had a very significant effect on tensile strength, elongation at break, and elasticity but it did not significantly affect the biodegradation time. The ratio of gadung tuber starch - glucomannan (60:40) with a gelatinization temperature of 85 ± 1oC produced the best bioplastic characteristics with a tensile strength value of 4.4 MPa, an elongation at break of 9.5%, and elasticity value of 22.390 MPa and resulted in a degradation time of 7 days. 2 variables meet the standards, namely: the extension when the bioplastic composites have broken up has met the SNI plastic standards and biodegradation has met the international plastic standard ASTM 5336. Keywords: bioplastic, composite, gadung starch, gelatinization temperature, glucomannan,